Kesan pendekatan pembelajaran koperatif teradun 'Flipped Classroom' terhadap prestasi dan tahap kemahiran koperatif pelajar dalam pembelajaran sains - Zainal, Nurhayati (2021)
Mastery of Science Subjects in schools is highly emphasized and various efforts to improve students' understanding have been implemented. Although students’ mastery levels were excellent, poor communication skills and lack of self - confidence can affect their group success. Several studies have found that cooperative learning methods integrated in blended teaching can help overcome the problem of existing achievement weaknesses and social interactions. Therefore, this study was conducted to examine the effect of the flipped classroom of blended cooperative learning approach for the topic of Animals towards students’ performance and level of cooperative skills. This study also examined the relationship between students’ performance and level of collaborative skills after using flipped classroom of blended cooperative learning approach for the topic of Animals. The research instruments involved Pre and Post Tests for Performance Tests of the topic of Animals and Cooperative Skills Rubric. The study involved 31 year 5 students from a primary school in the district of Johor Bahru. The study was conducted using the preexperimental design for one group in which the researchers studied one group for intervention during the experiment without a control group. The results of the study found that students' performance increased in the Post Test by 23.452 compared to the Pre Test. The results of the study also found that the flipped classroom of blended cooperative learning approach can help in improving students’ level of cooperative skills in the topic of Animals. This is due to the majority of students (83.9%) achieving an excellent level of collaboration skills. Furthermore, the results of the study showed that there was a significant relationship between students’ performance with the level of collaborative skills for the topic of Animals (rs = 0.403, p <0.05). This indicates that the level of students’ collaboration skills can influence students’ performance in the topic of Animals. In conclusion, the flipped classroom of blended cooperative learning approach is able to improve students’ performance and level of cooperative skills in Science learning.